Effect of supercritical CO2 plant extract and berry press cakes on stability and consumer acceptance of frozen Baltic herring (Clupea harengus membras) mince. (1st December 2020) - Damerau, Annelie; Kakko, Tanja; Tian, Ye; Tuomasjukka, Saska; Sandell, Mari; Hopia, Anu; Yang, Baoru
Highlights: Impact of antioxidants on stability of frozen fish mince were studied. Plant extract and berry press cakes inhibited lipid oxidation. Plant extract and berry press cakes performed better than common antioxidants. Addition of plant materials may pose a challenge to consumer acceptability. Abstract: A promising way of processing Baltic herring, Clupea harengus membras, is turning the fish into boneless mince. However, Baltic herring is prone to lipid oxidation, which possesses a challenge for industrial applications. The aim of this work was to study the efficacy of press cakes from Finnish berries and a supercritical CO2 plant extract to limit lipid oxidation during frozen storage of Baltic herring mince and to determine the impact of these additions on consumer acceptance in a fish product. Peroxide value, formation of volatile oxidation products and loss of polyunsaturated fatty acids showed that the tested natural additives decreased oxidation to a greater or similar extent as conventional antioxidants during 10-month storage. While potential of berry press cakes and plant extracts as "green label antioxidants" was shown, consumer study indicated need for further research to reach both optimal antioxidative efficacy and sensory properties.